Contours of biblical spirituality as a discipline - Huub Welzen (Acta Theologica)
Three approaches are used for coming towards a definition of Biblical spirituality. The first approach is from lived spirituality. We see always a bipolarity of text and reader. The reader attributes meaning to the text guided by the data of the text. The second approach is the analysis of literature discussing Biblical spirituality. There are many spiritualities both in the Bible and in its readers, influenced by their contexts. The third approach is the discussion of the composing terms. A definition is given: Biblical spirituality is about the divine human relational process in the Bible and about the Bible in the divine human relational process. A dialogue of spirituality and exegesis is needed. For doing research a threefold competence is needed: in exegesis, in spirituality and in the integration of these two. The final section is about intertextuality. Intertextuality may help to understand the spiritual process in reading biblical texts.